O uso de realidade virtual na simulação e treinamento de inseminação artificial em bovinos com dispositivos hápticos - Silva Júnior, Alexandre Ribeiro (2012)
The procedure of artificial insemination in cattle requires preparation and professional dexterity. In most cases, the training of fertilization is done through direct contact with animal itself. During periods of practical training, often is not possible a lot of students have contact with the animal, by factors like costs, risks to animal health and user, inappropriate physical space, cio and animal management. These factors end up making the learning process extremely theoretical, culminating no same unpreparedness. Accordingly, it is proposed a simulator of Artificial Insemination (SISTIA-ARITIFICIAL INSEMINATION TRAINING SYSTEM) with a model of appliance Reproduction veal, seen, among other factors, on: conduct training in a virtual environment, before leaving for the need of the practice in the real environment; decrease training costs, reduce expenses for the purchase of equipment, reduce risk with the student's health, since it is not exposed to contact with viruses and bacteria, reduce the risk of injury to the animal or real training error, monitor the results of training through the visualization of your data stored in a database of the simulation. The Virtual reality training simulation will be developed with the help of the Phantom haptic technology device Omini. The use of this type of device allows a closer interaction of the real world, since, among other factors, returns the user the sensation of stiffness, texture, size and strength of the object can improve performance, and intensify the feeling of immersion.